2010
DOI: 10.1063/1.3464776
|View full text |Cite
|
Sign up to set email alerts
|

The multiscale coarse-graining method: Assessing its accuracy and introducing density dependent coarse-grain potentials

Abstract: The ability of particle-based coarse-grain potentials, derived using the recently proposed multiscale coarse-graining (MS-CG) methodology [S. Izvekov and G. A. Voth, J. Phys. Chem. B 109, 2469 (2005); J. Chem. Phys. 123, 134105 (2005)] to reconstruct atomistic free-energy surfaces in coarse-grain coordinates is discussed. The MS-CG method is based on force-matching generalized forces associated with the coarse-grain coordinates. In this work, we show that the MS-CG method recovers only part of the atomistic fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 81 publications
1
72
0
Order By: Relevance
“…We are pursuing a bottoms-up method to develop these potentials (known as MS-CG), which effectively homogenizes atomistic information obtained from either QMD or classical MD into a particle based CG model. The details of this methodology and applications to nitromethane and RDX are detailed in recent publications [11,12]. In these, we have shown that CG MD results for structural, vibrational and elastic properties are in good agreement with atomistic simulation results for these systems, as well as agreement of shock properties, thus validating proper homogenization.…”
Section: Linking the Scalessupporting
confidence: 61%
“…We are pursuing a bottoms-up method to develop these potentials (known as MS-CG), which effectively homogenizes atomistic information obtained from either QMD or classical MD into a particle based CG model. The details of this methodology and applications to nitromethane and RDX are detailed in recent publications [11,12]. In these, we have shown that CG MD results for structural, vibrational and elastic properties are in good agreement with atomistic simulation results for these systems, as well as agreement of shock properties, thus validating proper homogenization.…”
Section: Linking the Scalessupporting
confidence: 61%
“…A pressure correction is applied to the potentials to match the pressure of the reference atomistic system. Although the relation between pressure on the CG and AA level is non-trivial (for instance, one cannot simultaneously reproduce both pressure and compressibility [44][45][46] ), we decide here on the pressure, in a similar way the adaptive resolution methods do, because we want to combine atomistic and CG models and they should have the same pressure. Details of the methods pertaining the current application are presented below.…”
Section: Coarse Grained Potentialsmentioning
confidence: 99%
“…Strictly speaking, this type of pressure correction is not formally correct in the case of force matching. Pressure correction for force matching does exist, 45,51 it is however not yet implemented in the VOTCA package.…”
Section: Coarse Grained Potentialsmentioning
confidence: 99%
“…In another group of approaches, one numerically generates CG interaction functions with the aim of reproducing the configurational phase space sampled in an atomistic reference simulation. These approaches may rely on different types of reference properties such as structure functions [77][78][79][80][81][82][83][84][85][86][87][88][89], mean forces [90][91][92][93][94][95] or relative entropies [96][97][98]. In the following subsection, a few basic notions of coarse-graining theory will be introduced, together with examples of the strategies that can be employed to perform the coarse-graining in practice.…”
Section: Coarse-grainingmentioning
confidence: 99%